2021
DOI: 10.3390/ijerph18020526
|View full text |Cite
|
Sign up to set email alerts
|

Making the Case for Proactive Strategies to Alleviate Homelessness: A Systems Approach

Abstract: Homelessness is a complex public health issue that affects some of the most vulnerable populations in the United States. This study takes a holistic approach to better understand and analyze the multiple factors and their interconnections that contribute to the complexity of this problem. A systems analysis was conducted by utilizing the system dynamics method, which allows analyzing and comparing trends and behavior of system outcomes for different “what if” scenarios, interventions, and policy implications. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…These previous studies analyzed the historical and developmental processes of the Korean professional baseball league based on literature reviews and empirical studies. However, when the authors of the current study discovered the complex system paradigm, a new perspective for seeing the world, we intuitively grasped the possible existence of a certain order and principle in the historical background and causes that led to the launch of the KBO League, thus representing a different view from the existing historical and social scientific analyses [15].…”
Section: Of 15mentioning
confidence: 94%
“…These previous studies analyzed the historical and developmental processes of the Korean professional baseball league based on literature reviews and empirical studies. However, when the authors of the current study discovered the complex system paradigm, a new perspective for seeing the world, we intuitively grasped the possible existence of a certain order and principle in the historical background and causes that led to the launch of the KBO League, thus representing a different view from the existing historical and social scientific analyses [15].…”
Section: Of 15mentioning
confidence: 94%
“…Homelessness in Spain has been extensively analyzed and studied since the 1990s, with research notably focusing on analyzing the homeless population and the different dimensions that shape their social exclusion [4][5][6][7][8][9]. This research has shown homelessness to be a complex issue that impacts the most vulnerable social groups, necessitating a comprehensive understanding of the various factors that impact the lives of those it affects [10]. The literature examining homelessness places particular emphasis on analyzing the factors that contribute to its appearance and persistence [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Three studies provide a broader lens on homelessness. Nourazari [ 11 ] uses a systems approach to consider policy implications, and Calvo [ 12 ] presents a 10-year review of mortality rates and risk factors. Magwood [ 13 ] examines introducing clinical guidelines supporting health equity.…”
mentioning
confidence: 99%